Relationship Of Learning Engagement And Classroom Incivility Of Islamic Education Religion Students In Jakarta - Muzaki Ramadhany; Dewi Anggraeni (Fikroh: Jurnal Pemikiran dan Pendidikan Islam, 2022)
This study discusses learning engagement and Islami education student classroom incivility in DKI Jakarta during the pandemic covid 19. Which is often impoliteness or classroom incivility occurred in the learning which ultimately makes learning becomes ineffective because the activeness of students in online learning is one of the main success factors in online learning and the achievement of learning objectives. This study uses a quantitative approach, this research sample is an Islamic education student in DKI Jakarta. Involving 215 respondents which sampling using the method questionnaire and observation. The results of this study indicate a negative relationship between learning engagement and classroom incivility for Islamic education student classroom incivility in DKI Jakarta with a significance result of -0,495.